Effects of family functioning and family hardiness on self-efficacy among college students - Tam, Cai Lian *; Tay, Ee Lin * (Sunway University College, 2007)
Family functioning has been related to numerous developmental problems. Although there are other factors affecting a student?s self-efficacy, this research focused on the effects of family functioning and family hardiness. The implications that family functioning plays a great role in shaping one?s self belief systems will help to emphasize the need to resolve a growing cycle of social issues. The objectives of this study is to find out whether family functioning and family hardiness will have an influence on students? self-efficacy and also to determine the level of difference in self-efficacy of male and female students. Participants involved in this study were made up of a random sample of 120 students from a few colleges in the state of Selangor. Results obtained from this research study showed that there is a correlation amongst all three variables used, namely, family functioning, family hardiness and self-efficacy are interrelated. In addition, the results also showed that more males than females have been categorized in the category of clinical group for family functioning and selfefficacy.